Tertiary treatment of secondary effluent using ultrafiltration for wastewater reuse: correlating membrane fouling with rejection of effluent organic matter and hydrophobic pharmaceuticals. Issue 4 (26th February 2019) - Qu, Fangshu; Wang, Hao; He, Junguo; Fan, Gongduan; Pan, Zhihui; Tian, Jiayu; Rong, Hongwei; Li, Guibai; Yu, Huarong
Abstract : Permeability loss and the low retention efficiency of soluble organics significantly restrict the application of ultrafiltration (UF) for water reclamation. Abstract : Permeability loss and the low retention efficiency of soluble organics significantly restrict the application of ultrafiltration (UF) for water reclamation. In this work, the tertiary treatment of secondary effluent using UF was investigated under a variety of transmembrane pressures (TMPs) (20–150 kPa) to obtain more insight into fouling by effluent organic matter (EfOM) and its impact on organic rejection, particularly for hydrophobic pharmaceuticals represented by carbamazepine and naproxen. The flux decline and the reversible fouling during secondary effluent filtration were substantially aggravated with increasing TMP, whereas the irreversible fouling was generally reduced, as attributed to restriction of EfOM adhesion to the membrane surface by the fouling layer. The fouling process was successively dominated by pore blocking and cake layer filtration, and the shift in the dominant mechanism was accelerated under higher TMPs. The rejection of EfOM was improved in the presence of a fouling layer, which acted as a secondary filtration medium, particularly at higher TMPs. The maximum rejection of hydrophobic pharmaceuticals by UF was observed in a moderate TMP range (40–60 kPa), probably due to a trade-off between increased fouling layer retention and reduced rejection due to increased wall shear and aggravated cake-enhanced concentration polarization with increasing TMP. The results would encourage the strategy of utilizing the fouling layer for irreversible-fouling restriction and better rejection of hydrophobic PhACs.